Feniks . biuletyn informacyjny RKW NSZZ "Solidarność" Region Gorzów Wlkp., no. 70, 1984 - "Solidarność" (Agencja Wydawnicza "Feniks", 1984)
Creation and circulation: From issue no. 1=190(29.IV.1989) published legally